A Retrospective Study of Coronary Artery Bypass Grafting with Low-Thermal Plasma Dissection Device Compared to Conventional Monopolar Electrosurgery - Uysal,Dincer (2021)
Abstract Introduction: The objective of this study is to compare the effects of conventional monopolar electrosurgery (CMES) and low-thermal plasma kinetic cautery (PKC) on complications such as bleeding, abnormal wound healing, pain, and drainage in patients who underwent on-pump coronary artery bypass grafting (CABG). Methods: This retrospective clinical study included 258 patients undergoing CABG; the patients were randomized to PKC (PEAK PlasmaBlade, n=153) and CMES (n=105) groups. The patients’ clinical data were examined retrospectively for biochemical variables, postoperative drainage, post-surgery erythrocyte suspension transfusion count, surgical site pain examined with visual analogue scale (VAS), and wound healing. Two-sided P-value > 0.05 was considered as statistically significant. Results: The median post-surgery erythrocyte suspension transfusion number was significantly lower with PKC compared to CMES (0 [0-1] vs. 1 [1-4], respectively, P<0.001). Mean postoperative drain output and time until removal of drain tubes were significantly lower with PKC compared to CMES (300±113 vs. 547±192 and 1.95±1.5 vs. 2.44±1.8; P<0.001 and P=0.025, respectively). Mean VAS score for spontaneous and cough-induced pain were significantly lower with PKC compared to CMES (1.98±1.51 vs. 3.94± 2.09 and 3.76±1.46 vs. 5.6±1.92; P<0.001 for both comparisons). Reoperation due to bleeding was significantly higher with CMES compared to PKC (0 vs. 11 [7.2%], P=0.001). Conclusion: Use of PKC during CABG considerably reduces postoperative drainage, need for blood transfusion, reoperation due to bleeding, and postoperative pain. PCK appears to be a good alternative to CMES for CABG.